THE EVOLVING ROLE OF DIGITAL TECHNOLOGIES IN THE TEACHER'S WORK - Abdullaho'jayeva Muattar Abdumajidovna; A. Azamatova Dilafro'z Saidganievna (Web of Journals Publishing, 2024)
This article examines the multifaceted role of digital technologies in the work of a teacher, the ways in which digital technologies influence the work of teachers.
Keywords: Digital technologies, differentiated learning, video conference, feedback.